2016
DOI: 10.3791/54071
|View full text |Cite
|
Sign up to set email alerts
|

Training Persons with Spinal Cord Injury to Ambulate Using a Powered Exoskeleton

Abstract: Powered exoskeletons have become available for overground ambulation in persons with paralyses due to spinal cord injury (SCI) who have intact upper extremity function and are able to maintain upright balance using forearm crutches. To ambulate in an exoskeleton, the user must acquire the ability to maintain balance while standing, sitting and appropriate weight shifting with each step. This can be a challenging task for those with deficits in sensation and proprioception in their lower extremities. This manus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
(73 reference statements)
0
51
0
Order By: Relevance
“…Several individual studies on specific exoskeletons and feasibility have been conducted. For example, the systems ReWalk [27,29,[39][40][41][42], Ekso [39,43,44], Indego [45,46], Exo-H2 [47], Arke [48], and X1 Mina [49] have been found to be practical for use. In addition to investigations of feasibility, several reviews have explored outcomes that relate to the efficacy of EAW.…”
Section: Lower Extremity Roboticsmentioning
confidence: 99%
“…Several individual studies on specific exoskeletons and feasibility have been conducted. For example, the systems ReWalk [27,29,[39][40][41][42], Ekso [39,43,44], Indego [45,46], Exo-H2 [47], Arke [48], and X1 Mina [49] have been found to be practical for use. In addition to investigations of feasibility, several reviews have explored outcomes that relate to the efficacy of EAW.…”
Section: Lower Extremity Roboticsmentioning
confidence: 99%
“…Powered exoskeletons enable persons with various walking problems to ambulate over the ground. Several of these devices require the use of crutches to ambulate and maintain balance (Wang et al, 2015 ; see Asselin et al, 2016 ). Beyond their obvious mechanical effects (Bateni and Maki, 2005 ), crutches are a critical source of somatosensory inflow that provides information about body orientation with respect to the supporting surface through “extended physiological proprioception” (Simpson, 1974 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found only one study [66] reporting falls, which occurred in three patients: two of them when they were starting to ambulate with forearm crutches, and the other patient fell down during a sit-to-stand transition (because of mechanical programming errors as mentioned in the original study). A total of 18 studies reported mild to moderate adverse events such as orthostatic hypertension [115,116], skin abrasions [21, 48, 64-66, 90, 110, 117-123], fatigue of the upper extremities [116,120], low back pain [66,91], and other adverse events such as urinary tract infections [119], talus fracture [119], dizziness [90], calcaneus fracture [116] and severe knee hyperextension [116]. Studies also described that skin abrasions were reduced using padding and size adjustments, and that fatigue of the upper extremities improved with practice.…”
Section: Safety and Risksmentioning
confidence: 99%